Agronomic performance of cultivars and advanced selections of strawberry in the South Plateau of Santa Catarina State - Zanin D.S.* (2019)
© 2019 Universidade Federal de Vicosa.Strawberry cultivation requires the use of cultivars adapted to the temperature and photoperiod conditions of the production region. The objective of this work was to evaluate cultivars and advanced selections of strawberry on productive performance and fruit quality, under the conditions of South Plateau of Santa Catarina State. The experiment was carried out in the municipality of Lages, in the 2016/2017 growing season. The cultivation system used was in the soil, in beds covered with black polyethylene film. The cultivars Camino Real, Benicia and Pircinque, and the selection CE 56 obtained the highest yields, above to 30 t ha-1. Benicia, Camino Real and Monterey, in turn, obtained the fruits with higher average fresh weight, around 24 g fruit-1. In the selections CE 51, CE 56, FRF 57.6, LAM 119.1, FRF 104.1, FRF PA 109.2 and the cultivars Benicia and Monterey the fruits of better quality were achieved, expressed by values of soluble solids / titratable acidity ratio above to 13. The cultivars Camino Real, Benicia and Pircinque, and the selection CE 56 performed as the most adapted to the region of study, among the genotypes evaluated.